Analisis Customer Value dan Quick Service terhadap Kepuasan Pelanggan di Connection 88 Cafe Medan - Rasyiqah, Siti Zharfa; Sembiring, Beby Karina Fawzeea; Situmorang, Syafrizal Helmi (Universitas Batanghari Jambi, 2024)
This research aims to determine and analyze the influence of customer value and quick service on customer satisfaction at Connection 88 Cafe Medan. The customer value provided by Connection 88 Cafe is considered to have not been fulfilled and customers also have not received good social recognition when they are at Connection 88 Cafe. The service provided by Connection 88 Cafe is also considered to be poor and customers feel uncomfortable with the quality of the food they receive. This research is associative research and the type of data used is quantitative data. The population in this study were Connection 88 Cafe customers in Medan City. The number of samples in this study was 140 people with a sampling technique using purposive sampling with the criteria of having made a purchase at Connection 88 Cafe Medan. Data analysis used multiple linear regression analysis. The results of this research show that simultaneously customer value and quick service have a positive and significant effect on customer satisfaction at Connection 88 Cafe Medan. Partially, customer value and quick service have a positive and significant effect on customer satisfaction at Connection 88 Cafe Medan.